ANALISIS HUBUNGAN KEDISIPLINAN BELAJAR DARI RUMAH (BDR) DENGAN PRESTASI BELAJAR KIMIA SISWA SELAMA MASA PANDEMI - VINA N VAN HARLING (SOSCIED, 2020)
Learning from home shows good results if there is success in learning which is influenced by factors from within and from outside the students themselves. One of them is a discipline in learning. The purpose of this study was to determine whether there is a relationship between discipline in learning from home and the learning achievement of chemistry students of Class XI IPA SMA Negeri 3 Sorong during the Covid-19 pandemic. The number of samples was determined using the Harry King Nomogram with a 95% confidence interval to obtain 154 samples from 254 populations. This research uses correlational research. The results of the correlation test showed that the correlation coefficient (r) between the discipline of learning from home and the students' chemistry learning achievement was 0.066 with p = 0.419, and with a positive correlation direction. By using a significance level of 5%, it was obtained p = 0.419> 0.05. The correlation value obtained from the results of the analysis is the same as rxy ≤ 0, which means that Ho is accepted and Hi is rejected, or in other words, there is no positive and significant relationship between the discipline of learning from home and the chemistry learning achievement of students of class XI IPA SMA Negeri 3 Sorong during the pandemic. Covid-19. This means that students' chemistry learning achievement during the Covid-19 pandemic was not influenced by the level of student learning discipline.